Hypoxia and tumor angiogenesis in the era of hepatocellular carcinoma transarterial loco-regional treatments. (1st May 2018) - Petrillo, Mario; Patella, Francesca; Pesapane, Filippo; Suter, Matteo B; Ierardi, Anna M; Angileri, Salvatore A; Floridi, Chiara; de Filippo, Massimo; Carrafiello, Gianpaolo
This review focuses upon interactions and potential therapeutic targets in the 'vicious cycle' between hypoxia and neoangiogenesis following treatment of hepatocellular carcinoma with transarterial loco-regional therapies. Biomarkers correlated with angiogenesis have been studied by many authors as prognostic determinants following transarterial intrahepatic therapy. According to these results future therapies directed toward specific factors related to angiogenesis could play a significant role in preventing local tumor recurrence and remote metastasis.